Choosing the sport between parents and children: reasons in comparison - Biino, Valentina; Giuriato, Matteo; Zaninelli, Mario; Lovecchio, Nicola (Formazione & insegnamento, 2020)
The reasons that lead to start a sport have been studied in the recent years. In this framework, the intrinsic motivation paly a crucial role as the stimulus for an external behavior: both for parents and children. The aims of this re-search was to evaluate which motivations drive children and their parents in the sport adherence.